Rancang Aplikasi Sistem Informasi Bank Soal Dan Analisis Butir Soal Di Fakultas Kedokteran XYZ - Dinar Mustofa; Anggit Wirasto; Abdul Ghofur (Informasi Interaktif, 2021)
Higher education in health has a very important role in providing quality human resources. The quality referred to is closely related to the quality of lecturers and the learning evaluation system so that university graduates will be ready and able to follow the policy of implementing the graduate competency test as a requirement for obtaining a competency certificate and registration certificate (STR). In practice, the evaluation of student learning generally uses a computer-based examination model (Computer Based Test - CBT). The questions written by the question writers were inputted into the CBT application to be tested on students. The problem faced is that there is no analysis of the questions that have been tested so that students do not get detailed feedback on the results of their exams. Likewise, the question writers could not know the quality of the questions they wrote.Keywords: Information System, Computer Based Test, Item Bank Administration